An examination of the Northern Irish sea fishing industry - Hughes, P. H. (Statistical and Social Inquiry Society of Ireland, 1968)
The Northern Irish sea fishing industry is of the in-shore type, the boats seldom being absent from port for more than eighteen or twenty hours at a time. By almost any standard these boats are up to date and well equipped. I have heard the fleet described by men of experience as the most modern in the United Kingdom. This might be; however, ultimately the success of the fishing must depend on its strength and success as a marketing unit and it will be necessary to look at the fleet both as a catching unit and as a marketing unit, as being equally concerned with demand as it is with supply.
Read before the Society, 6 May 1968.
Keywords: Northern Ireland fishing industry; Productivity; Fish demand; 314.15